Analysis of Non-Physical Work Environment and Motivation to Employee Performance on CV. Adikarya Sukses Engineering Jombang - Aryo Seno Pambudi; Gendut Sukarno; Endang Iryanti (International Journal of Economics (IJEC), 2023)
This study aims to examine the concept of non-physical work environment and motivation to employees performance on CV. Adikarya Sukses Engineering Jombang. This research is expected to provide input to the company in managing employee performance, especially related to non-physical work environments and motivation. The object of this study is CV. Adikarya Sukses Engineering Jombang, with primary and secondary data sources. The population in this study was 55 employees on CV. Adikarya Sukses Engineering Jombang with a saturated sample technique of 55 people as respondents. The analysis technique used in this study is SmartPLS (Partial Least Square) 4.0 with the instrument testing used is outer model test, inner model test and hypothesis test. The test results can be concluded that non-physical work environment variables and motivation variables have a positive effect and contribute to employee performance on CV. Adikarya Sukses Engineering Jombang.